Efektivitas Campuran Ekstrak Daun Kelor (Moringa oleifera) dan Serai Wangi (Cymbopogon nardus l) Terhadap Mortalitas Larva Nyamuk Aedes aegypti - Hidayah, Nurul; Kurnianto, Ady; Bhelo, Angela; Palgunadi, Bagus Uda (VITEK : Bidang Kedokteran Hewan, 2021)
This study aimed to determine the effectiveness of a mixture of Moringa leaf extracts (Moringa oleifera) and citronella (Cymbopogon nardus L)on the mortality of mosquito larvae Aedes aegypti. Experimental animals used in this study mosquito larvae Aedes aegypti were 625. The design used was a completely randomized design with 5 treatments and 5 replications. The five treatments were the treatment group consisting of concentrations of 2%, 4% and 6% and the control group consisting of positive control, namely abate and negative control, namely aquades. Mosquito larvae mortality was observed every 2 hours for 12 hours. The data obtained were analyzed using one way ANOVA test and continued with Duncan's test. The results obtained in the mixed treatment of Moringa leaf extract and lemongrass 4% and 6% had high larvicidal ability and were the same as positive control themepos (abate). Based on the results of the study, it was concluded that a mixture of Moringa leaf extracts (Moringa oleifera) and citronella (Cymbopogon nardus L)had larvicidal ability against mosquito larvae Aedes aegypti.